Temperature And Humidity Test Of The Telemetry Tool Modeling In Baby Incubator - Ansor Usman; Hendra Marwazi; Samsul Alam (Politeknik Kesehatan Kemenkes Jakarta II, 2018)
Modeling tool is made an attempt to help health care in special hospitals for care in obstetrics and perinatology space. This study used temperature setting range is from 34 ° C to 38 ° C, while for setting the humidity of the range of 0% to 100%, is divided into two parts, namely the design of hardware and software. Tests conducted in the Laboratory of the Department of Health Polytechnic Elektromedik Jakarta II. Design manufacture of modules that do get into the telemetry monitoring system applications, where telemetry tool can be used to monitor the value of an object located at a remote distance applied to medical devices, which will be monitored temperature and humidity is a very important part in the incubator tool baby. The results of modeling design includes testing of skin temperature in the incubator, the test measurement of skin temperature and humidity in the telemetry receiver, test measurement of skin temperature on the thermometer, hygrometer humidity in the test measurement. With the results of the five test measurement was still below the threshold of 10%. It can be concluded that the telemetry tool can perform accurate distance measurement, in accordance with the amount of heat generated by the source and the humidity is a tool incubator. This research can be developed to monitor the temperature and humidity with computer based.